A research of subjective evaluations of the thermal comfort of business clothing evaluated in warm and slightly cold environment - Celcar, Damjana (Tekstilna industrija, 2020)
This paper presents a study of subjective assessments of thermal comfort when wearing business clothing made from conventional textiles, such as wool and blends with wool and textiles combined with phase-change materials (PCMs), which are capable of providing adequate thermal physiological comfort to the wearer. The evaluation of thermal comfort was carried out on the basis of determining the subjective feeling of thermal comfort with the help of test subjects in a computer controlled climatic chamber, in artificially created warm and slightly cold environmental conditions, at ambient temperature of 25°C, 20°C, 15°C and 10°C. The impact of particular business clothing systems and varied environmental conditions on the wearer's subjective feeling of thermal comfort was determined with a questionnaire and an assessment scale of thermal comfort defined by standard ISO 10551:1995. For this purpose, an analysis of the subjective evaluation of thermal comfort, the desired thermal state, the acceptability of the current situation and their personal tolerance of the environment, was made before, during and after each experiment. The results of the research show that subjective evaluations of thermal comfort directly depend on environmental conditions, as well as clothing systems and activity levels. It was found that the test subjects felt most comfortable in the selected business clothing at an ambient temperature of 20°C and 15°C. It is also evident from the results that at an ambient temperature of 25°C, the persons in the selected clothing felt slightly uncomfortable, especially during and after walking when they felt hot. The test subjects felt uncomfortable also at an ambient temperature of 10°C, when they felt cold or slightly cold while wearing the analysed 3-layer clothing systems without an additional layer of clothing. This indicates that an additional layer of clothing, such as a coat is needed for performing adequate thermal comfort around and below 10°C.